2022
DOI: 10.1186/s40560-022-00597-5
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of combination triple therapy with vasopressin, steroid, and epinephrine in cardiac arrest: a systematic review and meta-analysis of randomized-controlled trials

Abstract: Background This study investigated whether combination therapy with vasopressin, steroid, and epinephrine (VSE) improves in-hospital survival and return of spontaneous circulation (ROSC) during and after resuscitation in-hospital cardiac arrest (CA). Materials and methods Various databases were explored from inception until October 2021 for relevant published clinical trials and cohort studies. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 57 publications
0
4
0
1
Order By: Relevance
“…A difference between our study and those two recent studies29 30 by Granfeldt et al and Saghafi et al is that we evaluated the overall impact of vasopressin in cardiac arrest. There is no single optimal method suitable for all patients.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…A difference between our study and those two recent studies29 30 by Granfeldt et al and Saghafi et al is that we evaluated the overall impact of vasopressin in cardiac arrest. There is no single optimal method suitable for all patients.…”
Section: Discussionmentioning
confidence: 79%
“…The conclusion coincides with the results from our study. Moreover, a meta-analysis by Saghafi et al 30 suggested that VSE combination therapy during and after IHCA may have beneficial effects in terms of the ROSC, Open access renal and circulatory failure free days, and mean arterial pressure. In our study, three trials [12][13][14] receiving VSE were included, and three trials used the same VSE protocol during CPR, as shown in table 2.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, 0.5 mg to more than 10 mg epinephrine has been administered through intravenous, intracardiac, endobronchial, and intraosseous routes [6]. Epinephrine is an active sympathomimetic hormone that stimulates the alpha-(α) and beta (β)-adrenergic systems during cardiopulmonary resuscitation [7], thus increasing the probability of achieving return of spontaneous circulation (ROSC). According to previous studies, stimulation of the alpha (α) receptor on the vascular smooth muscles leads to vasoconstriction, which increases aortic diastolic and perfusion pressure to optimize the probability of attaining ROSC [8].…”
Section: Description Of Intervention (Inotropes)mentioning
confidence: 99%
“…У выживших после остановки сердца тяжелые церебральные нарушения встречаются в 25-50% случаев [18]. В исследовании Andersen et al неврологический статус измерялся по шкале CPC, благоприятный неврологический исход наблюдался у 7,6% пациентов как в группе вмешательства, так и в контрольной группе во время первого цикла СЛР, на 30-й день без существенной разницы между двумя группами исследования (значение p> 0,99) [19]. Неврологически благоприятная выживаемость до выписки из больницы оценивалась в исследовании Mentzelopoulos et al, где неврологическая недостаточность определялась по шкале комы Глазго (ШКГ) <9 баллов.…”
Section: актуальностьunclassified